Effects Of Different Empirical Design Approaches For Size Galleries On The Behaviour Of Rock Masses During The Excavation Operation: Excavation Case At BAE Well - et. al., Ismail Zaki, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The characterization of rock massifs is a delicate job; indeed, it is possible to understand the behaviour of intact rocks individually by laboratory tests but it is difficult to characterize them on the whole rock mass, which has undergone a complex geological history. Empirical approaches play an important role in the excavation of galleries and the design of support systems. These approaches are considered very effective in optimizing the tunnel excavation process. Several reliable empirical approaches have been developed, but the selection or use of an appropriate empirical method to design the tunnel excavation remains a difficult task. Therefore, in this work, the analysis of four approaches, the most used, of different empirical design was carried out to determine the behaviour of the rock mass during its excavation in a state of high in situ stress. This study was carried out on the scale of the ST2 rock mass of the worksite (BAE well 3) at the Bouazzer mine. These approaches include the AFTES classification, rock mass index (RMR), rock mass quality (Q) and geological resistance index (GSI). Based on the simulated statistical results obtained from said empirical approaches, through the finite element calculation, it was found that the application of the rock mass quality approach is very efficient in the excavation of the rock mass. gallery of size because it makes it possible to take into account the equivalent dimensions of the gallery, the stress condition in situ due to the excavation and the heights of overburden which are considered as major elements of the stability of the gallery. The method provides an optimized reinforcement and support design. In addition, this study will serve as a valuable basic document for the geotechnical engineer to design and plan support systems in the excavation of galleries under high in-situ stress.